Enhancing attitudes and self-efficacy toward inclusive teaching in physical education pre-service teachers: Results of a quasi-experimental study in physical education teacher education - Grimminger-Seidensticker, Elke; Seyda, Miriam (Frontiers in Education, 2022)
As many teachers feel overwhelmed by teaching inclusively, teacher education programs have to find ways to prepare them for this future challenge. Due to particular conditions, physical education (PE) teachers might be a particular target group in this context. With regard to the state of research, there is a need to identify inputs or learning situations that might improve the best physical education teachers’ competencies and underlying cognitive and affective-motivational aspects, such as attitudes, self-efficacy, or stress perception, to empower physical education teachers for teaching physical education inclusively. Practical experiences seem to be a key aspect in this context. Therefore, we conducted a quantitative evaluated quasi-experimental intervention study with physical education pre-service teachers to test different forms of promoting inclusion competencies and their underlying cognitive and affective-motivational constructs. Intervention group 1 (IG 1) followed an information-based seminar, whereas intervention group 2 (IG 2) was also taught theoretical units in combination with practical lessons in the gym that were prepared and conducted by the pre-service teachers themselves. The control group (CG) did not receive any specific information or practical experiences on inclusively teaching physical education. We first hypothesized that both intervention groups (IG 1 and IG 2), in contrast to the control group, would significantly improve their attitudes toward inclusion and the self-efficacy to teach inclusively, and would decrease their perceived stress related to teaching physical education inclusively (hypothesis 1). Second, we hypothesized that participants of intervention group 2 would have a significantly stronger increase in positive attitudes toward inclusion, a stronger increase in self-efficacy, and a greater decrease in the level of perceived stress related to teaching physical education inclusively than participants of intervention group 1 (hypothesis 2). Based on ANCOVA analysis, we found significant results for some subscales of the attitudes, but no significant results for stress perception and self-efficacy. In total, the teaching strategy in intervention group 2 seemed to work best in enhancing physical education pre-service teachers’ inclusion competencies.